Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To find [tex]\( (f \circ g)(x) \)[/tex], which denotes the composition of functions [tex]\( f \)[/tex] and [tex]\( g \)[/tex], we need to evaluate [tex]\( f(g(x)) \)[/tex].
Given:
[tex]\[ f(x) = 2x - 7 \][/tex]
[tex]\[ g(x) = 4x^2 + 2x + 6 \][/tex]
Let's break it down step-by-step:
1. Evaluate [tex]\( g(x) \)[/tex] first:
We need to determine [tex]\( g(x) \)[/tex] for a specific value of [tex]\( x \)[/tex]. We'll use [tex]\( x = 1 \)[/tex]:
[tex]\[ g(1) = 4(1)^2 + 2(1) + 6 \][/tex]
Calculate the value:
[tex]\[ g(1) = 4 \cdot 1 + 2 \cdot 1 + 6 \][/tex]
[tex]\[ g(1) = 4 + 2 + 6 \][/tex]
[tex]\[ g(1) = 12 \][/tex]
Therefore, [tex]\( g(1) = 12 \)[/tex].
2. Now evaluate [tex]\( f(g(x)) \)[/tex]:
We need to find [tex]\( f \)[/tex] at the value [tex]\( g(1) \)[/tex], which we found to be 12. So, evaluate [tex]\( f(12) \)[/tex]:
[tex]\[ f(12) = 2(12) - 7 \][/tex]
Calculate the value:
[tex]\[ f(12) = 24 - 7 \][/tex]
[tex]\[ f(12) = 17 \][/tex]
Hence, [tex]\( f(g(1)) = 17 \)[/tex].
From the steps above, we have determined:
- [tex]\( g(1) = 12 \)[/tex]
- [tex]\( (f \circ g)(1) = 17 \)[/tex]
Therefore, the result of the composition is:
[tex]\[ (f \circ g)(x) = 17 \quad \text{when} \quad x = 1 \][/tex]
Given:
[tex]\[ f(x) = 2x - 7 \][/tex]
[tex]\[ g(x) = 4x^2 + 2x + 6 \][/tex]
Let's break it down step-by-step:
1. Evaluate [tex]\( g(x) \)[/tex] first:
We need to determine [tex]\( g(x) \)[/tex] for a specific value of [tex]\( x \)[/tex]. We'll use [tex]\( x = 1 \)[/tex]:
[tex]\[ g(1) = 4(1)^2 + 2(1) + 6 \][/tex]
Calculate the value:
[tex]\[ g(1) = 4 \cdot 1 + 2 \cdot 1 + 6 \][/tex]
[tex]\[ g(1) = 4 + 2 + 6 \][/tex]
[tex]\[ g(1) = 12 \][/tex]
Therefore, [tex]\( g(1) = 12 \)[/tex].
2. Now evaluate [tex]\( f(g(x)) \)[/tex]:
We need to find [tex]\( f \)[/tex] at the value [tex]\( g(1) \)[/tex], which we found to be 12. So, evaluate [tex]\( f(12) \)[/tex]:
[tex]\[ f(12) = 2(12) - 7 \][/tex]
Calculate the value:
[tex]\[ f(12) = 24 - 7 \][/tex]
[tex]\[ f(12) = 17 \][/tex]
Hence, [tex]\( f(g(1)) = 17 \)[/tex].
From the steps above, we have determined:
- [tex]\( g(1) = 12 \)[/tex]
- [tex]\( (f \circ g)(1) = 17 \)[/tex]
Therefore, the result of the composition is:
[tex]\[ (f \circ g)(x) = 17 \quad \text{when} \quad x = 1 \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.